Contribution of Sex Differences to Development of Cardiovascular Disease in Metabolic-Associated Steatotic Liver Disease (MASLD) - Lucy C. Taylor; Gertrude Arthur; Marcella de Carvalho Cruz; David E. Stec; Olufunto O. Badmus (International Journal of Translational Medicine)
Sex differences are a complex and crucial variable in developing and progressing metabolic and cardiovascular disease pathophysiology and clinical outcomes. The female sex, compared to the male sex, is protected from metabolic disturbances and their resulting cardiovascular events. However, the peculiar life phases associated with females, such as puberty, pregnancy, and premenopausal and menopausal stages, are all associated with different risks for the development of cardiovascular disease (CVD). Metabolic dysfunction-associated steatotic liver disease (MASLD), a condition of hepatic steatosis, and at least one feature of metabolic syndrome is associated with an increased risk of cardiovascular events. The risk of MASLD and its progression to the development of CVD differs between men and women. Differences in several factors, including formyl peptide receptor (FPR) 2, adipose tissue distribution, liver pyruvate kinase (LPK), and ketone body production, may underlie the sex differences in the risk of development of MASLD-induced CVD. Understanding the specific risk factors involved in the development and progression of MASLD between the sexes is crucial. This knowledge will provide important insights into the mechanisms responsible for its cardiovascular complications and can potentially lead to therapeutics targeted explicitly for each sex, offering new hope in the fight against MASLD-induced CVD.